Straminergon and Calliergon (Calliergonaceae, Bryopsida) in the Iberian Peninsula - Oliván, Gisela; Fuertes, Esther; Acón, Margarita (Lazaroa, 2006)
The genera Straminergon Hedenäs and Calliergon (Sull.) Kindb. are revised for the Iberian Peninsula, based mainly on herbarium specimens kept in PC and the main Iberian herbaria. The occurrence of Straminergon stramineum (Dicks. ex Brid.) Hedenäs, Calliergon cordifolium (Hedw.) Kindb. and C. giganteum (Schimp.) Kindb. in the studied area is confirmed. S. stramineum grows mainly in fens in the mountainous areas of the northern half of the Iberian Peninsula and Sierra Nevada. C. cordifolium is restricted to fens or wet meadows in the alpine regions of the northern third of the peninsula (Pyrenees, Cantabrian Range and north-western part of the Iberian Range), while the localities in the Central Range, previously recorded in the bibliography, are excluded after this study from its distribution area. C. giganteum has been collected only in fens in the Eurosiberian Region, in one locality in the Pyrenees and four in the Cantabrian Range. Keys, descriptions, illustrations, SEM photographs and distribution maps of the species of Straminergon and Calliergon in the Iberian Peninsula are provided.